Effects of soil enhancer (XXL) on yield attributes of BRRI dhan29 and hybrid dhan TAJ1 cultivars of rice in boro season - Rahman, Md Saidur; Haque, Md Moinul; Ahamed, Kamal Uddin (Bangladesh Journal of Botany, 2018)
The present study used two varieties (BRRI dhan29 and Hybrid dhan Taj1) of rice and (control) and six different concentrations of soil enhancer XXL [125% (1.88/1.5 g/l), 100% (1.5/1.5 g/l), 75% (1.125/1.5 g/l), 50% (0.75/1.5 g/l), 33% (0.50/1.5 g/l) and 25% (0.38/1.5 g/l)] with recommended doses of (N, P, K, S and Zn) fertilizers. Significant variation was observed in different yield contributing characters with soil enhancer (XXL) application. Among the different soil enhancer (XXL) concentrations, 75% XXL provided the highest yield (10.58 t/ha). With 75% XXL, BRRI dhan29 and Hybrid dhan Taj1 provided their highest grain yield (11.09 t/ha and 10.07 t/ha, respectively). However, BRRI dhan29 performed well due to yield attributes (fertile tillers/hill, panicle length and shoot dry matter/hill which were 11.94, 23.95 cm and 21.59 g, respectively) than that of Hybrid dhan Taj1 with 75% XXL applied.